Diffusion of small solute particles in viscous liquids: cage diffusion, a result of decoupling of solute-solvent dynamics, leads to amplification of solute diffusion - Acharya, Sayantan; Nandi, Manoj K.; Mandal, Arkajit; Sarkar, Sucharita; Bhattacharyya, Sarika Maitra (Journal of Physical Chemistry B, 2015)
We study the diffusion of small solute particles through solvent by keeping the solute solvent interaction repulsive and varying the solvent properties. The study involves computer simulations, development of a new model to describe diffusion of small solutes in a solvent, and also mode coupling theory (MCT) calculations. In a viscous solvent, a small solute diffuses via coupling to the solvent hydrodynamic modes and also through the transient cages formed by the solvent. The model developed can estimate the independent contributions from these two different channels of diffusion. Although the solute diffusion in all the systems shows an amplification, the degree of it increases with solvent viscosity. The model correctly predicts that when the solvent viscosity is high, the solute primarily diffuses by exploiting the solvent cages. In such a scenario the MCT diffusion performed for a static solvent provides a correct estimation of the cage diffusion.

Fickian yet non-Gaussian behaviour: A dominant role of the intermittent dynamics - Acharya, Sayantan; Nandi, Ujjwal Kumar; Bhattacharyya, Sarika Maitra (Journal Of Chemical Physics, 2017)
We present a study of the dynamics of small solute particles in a solvent medium where the solute is much smaller in size, mimicking the diffusion of small particles in crowded environment. The solute exhibits Fickian diffusion arising from non-Gaussian Van Hove correlation function. Our study shows that there are at least two possible origins of this non-Gaussian behaviour: the decoupling of the solute-solvent dynamics and the intermittency in the solute motion, the latter playing a dominant role. In the former scenario when averaged over time long enough to explore different solvent environments, the dynamics recovers the Gaussian nature. In the case of intermittent dynamics the non-Gaussianity remains even after long averaging and the Gaussian behaviour is obtained at a much longer time. Our study further shows that only for an intermediate attractive solute-solvent interaction the dynamics of the solute is intermittent. The intermittency disappears for weaker or stronger attractions. Published by AIP Publishing.

Comparative study of anomalous size dependence of charged and neutral solute diffusion in water - Acharya, Sayantan; Nandi, Ujjwal K.; Bhattacharyya, Sarika Maitra (Journal of Physical Chemistry B, 2019)
We present a comparative study of size dependence of diffusion for charged and neutral solutes in water. Although both show nonmonotonicity of the size dependence of diffusion, their nature and origin are quite different. For neutral solutes, the peak position and the value of diffusion at the maximum are both independent of the solute water interaction. Interestingly, for charged solutes, with an increase in solute water interaction strength, the peak position shifts to lower solute sizes and with an increase in charge, it shifts to higher solute sizes. The diffusion value at the peak reduces with an increase in both solute water interaction and solute charge. We show that all these features observed for charged solutes can be understood in terms of the interplay between ionic and nonionic interactions which is definitely absent for neutral solutes. Some of the earlier studies addressing the nonmonotonicity in diffusion did suggest the interplay between the two interactions to be the cause. However, this is the first time we show that such an interplay gives rise to the nonmonotonicity in the potential energy which is a prerequisite for obtaining the nonmonotonicity in the diffusion. Such nonmonotonicity in the potential energy is absent for neutral solutes.

Fickian yet non-Gaussian behaviour: A dominant role of the intermittent dynamics (vol 146, 134504, 2017) - Acharya, Sayantan; Nandi, Ujjwal Kumar; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2019)